Estetika Gerak Tari Sambut Sebiduk Sehaluan di Kabupaten OKU Timur - Julta, Arbi; Sari, Eka (ALACRITY : Journal of Education, 2025)
The Sebiduk Sehaluan Welcome Dance is a dance that is performed in groups. As a form of honor and respect for the guest of honor who came to Martapura, East OKU Regency, this dance is a form of joy and respect for the arrival of the guest of honor from the local community to the Bumi Sebiduk Sehaluan area. This research aims to evaluate the aesthetics of the dance movements in the Sambut Sebiduk Sehaluan Dance. Using a qualitative descriptive approach, an ethical and emic approach, and a choreographic aesthetic approach, this research methodology is qualitative, using interview, observation, and documentation data collection techniques—the data analysis technique used by Adshead Theory, et al. The research results obtained are the value of beauty in the Sambut Sebiduk Sehaluan Dance where the unique beauty is created from the intertwining patterns of time, place, and use of energy which are the characteristics of the movement. The use of a wide and varied tempo and a high level of energy in the volume of movement creates a lively, seductive, and enthusiastic impression.